Dichlorinated Organic‐Salt Terahertz Sources for THz Spectroscopy. Issue 4 (14th December 2022) - Shin, Bong‐Rim; Yu, In Cheol; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Sang‐Wook; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract: Although in terahertz (THz) source materials molecular anions significantly influence the performance of THz generation, only limited classes of molecular counter anions have been reported. Here, utilizing dichlorinated molecular anions in THz generators is reported for the first time, to the best of our knowledge. In these new crystals, two dichlorinated molecular anions with different molecular symmetries, asymmetric 3, 4‐dichlorobenzenesulfonate (34DCS) and symmetric 3, 5‐dichlorobenzenesulfonate (35DCS), are incorporated with a 2‐(4‐hydroxystyryl)‐1‐methylquinolinium (OHQ) cation possessing top‐level molecular optical nonlinearity. OHQ‐34DCS exhibits a strong nonlinear optical response, in contrast to OHQ‐35DCS. In OHQ‐34DCS crystals, the dichlorinated groups form strong halogen bonds (XBs) and hydrogen bonds (HBs), which are beneficial for suppressing molecular (phonon) vibrations. The optical‐to‐THz conversion efficiency of the OHQ‐34DCS crystals is extremely high, comparable to that of the benchmark organic THz generators. Moreover, the THz emission spectra from the OHQ‐34DCS crystals, compared to those of previously reported benchmark analogous crystals, are stronger modulated toward a flatter shape, but possess substantially reduced spectral dimples. Therefore, the introduction of dichlorinated molecular anions is an efficient approach for the design of highly efficient electro‐optic salt crystals as efficient broadband THz wave sources. Abstract : Organic‐salt terahertz sources, utilizing dichlorinated aromatic molecular anions for the first time to the best of our knowledge, exhibit state‐of‐the‐art optical‐to‐THz conversion efficiency and a flat spectral shape. In newly designed highly efficient nonlinear optical organic crystals, the dichlorinated groups form strong halogen bonds as well as hydrogen bonds that are beneficial for reducing the self‐absorption of terahertz source crystals.